Double gene targeting multiplex polymerase chain reaction–restriction fragment length polymorphism assay discriminates beef, buffalo, and pork substitution in frankfurter products - Hossain, Motalib A.Motalib; Ali, Md. Eaqub; Abd Hamid, Sharifah Bee; Asing, Asing; Mustafa, Shuhaimi; Mohd Desa, Mohd Nasir; Sarker, Md. Zaidul Islam (American Chemical Society, 2016)
Beef, buffalo, and pork adulteration in the food chain is an emerging and sensitive issue. Current molecular techniques to authenticate these species depend on polymerase chain reaction (PCR) assays involving long and single targets which break down under natural decomposition and/or processing treatments. This novel multiplex polymerase chain reaction–restriction fragment length polymorphism assay targeted two different gene sites for each of the bovine, buffalo, and porcine materials. This authentication ensured better security, first through a complementation approach because it is highly unlikely that both sites will be missing under compromised states, and second through molecular fingerprints. Mitochondrial cytochrome b and ND5 genes were targeted, and all targets (73, 90, 106, 120, 138, and 146 bp) were stable under extreme boiling and autoclaving treatments. Target specificity and authenticity were ensured through cross-amplification reaction and restriction digestion of PCR products with AluI, EciI, FatI, and CviKI-1 enzymes. A survey of Malaysian frankfurter products revealed rampant substitution of beef with buffalo but purity in porcine materials.